Cognition, emotion and trust: A comparative analysis of Cambodia's perceived and projected online image. (December 2019) - Iordanova, Elitza; Stainton, Hayley
A comparative analysis of information on Cambodia as a tourist destination published on official tourism websites and amateur travel blogs suggests that there are substantial differences in the way Cambodia's destination marketers and commercial enterprises promote the destination and the way travel bloggers perceive it and write about it. Cambodia's projected online image elicited through the analysis of official tourism websites consists of mainly cognitive image elements (knowledge and beliefs about Cambodia), whereas its perceived image obtained from amateur travel blogs contains both cognitive and affective (feelings and attitudes towards Cambodia) image elements. Furthermore, the 'friend'-style relationship that the reader develops with the travel blogger can be attributed to personal projections and thus induces an element of trust not established between the reader and the websites. Findings suggest that a lack of perceived trust among destination marketers and an increased level of trust among authors of user-generated content (UGC) and their readers has led to destination marketers being at a distinct disadvantage compared with their blogging colleagues. The use of affective evaluations of destinations by bloggers alongside their perceived credibility is likely to weigh more heavily in consumer's decision-making process than promotional material presented by the likes of tourist boards and commercial enterprises. The theoretical and practical implications of these findings are also discussed.